Pengaruh Purifikasi n-Heksana pada Serbuk Simplisia terhadap Kadar Asiatikosida, Penangkapan Radikal Bebas dan Kadar Fenol Total Ekstrak Etanolik Herba Pegagan (Centella asiatica (L.) Urban) - AGATHA BUDI SUSIANA LESTARI; ACHMAD FUDHOLI; AKHMAD KHARIS NUGROHO; ERNA PRAWITA SETYOWATI (Fakultas Farmasi Universitas Pancasila, 2015)
It has been proven that gotu kola (Centella asiatica (L.) Urban) have an antioxidant activity that make it possible to use in preventing degenerative illness. The aims of this study are to find the effect of n-hexane purification before maceration on asiaticoside content, free radical scavenging activity and total phenolic content of gotu kola ethanolic extract. The gotu kola extract was made by maceration process using the mix of ethanol and aquadest as solvents in different proportion, which are 100%:0% (E100), 75%:25% (E75), 50%:50% (E50), 25%:75% (E25), and 0%:100% (E0). The determination of asiaticoside content in gotu kola ethanolic extract was measured using Thin Layer Chromatography (TLC) Densitometry method, free radical scavenging activity was measured using diphenylpicryl hydrazyl (DPPH) and defined by parameter of IC , and total phenolic content was defined by equivalency of galic acid using Folin-Ciocalteau. The results show that the hexane purification would increasing total phenolic content significantly in ethanolic extract which extracted with solvents in proportion of ethanol:aquades 75%:25% (E75), 50%:50% (E50), and 25%:75% (E25), but not significant in decreasing of IC . Statistically, n-hexane purification was also not significant to increasing asiaticoside content in gotu kola ethanolic extract.